Transperitoneal versus retroperitoneal laparoscopic adrenalectomy for large pheochromocytoma: Comparative outcomes. (14th November 2018) - Shiraishi, Koji; Kitahara, Seiji; Ito, Hideaki; Oba, Kazuo; Ohmi, Chietaka; Matsuyama, Hideyasu
Abstract : Objectives: To evaluate operative and oncological outcomes of laparoscopic adrenalectomy through a transperitoneal approach and retroperitoneal approach for large (>5 cm in diameter) pheochromocytomas. Methods: We retrospectively compared the results of a transperitoneal approach with those of a retroperitoneal approach in 22 patients (mean age 57.5 years, range 38–76 years) with unilateral large pheochromocytomas (12 right, 10 left). The mean body mass index, operation time, pneumoperitoneum time, estimated blood loss, fluctuation in blood pressure and complication rate were compared between the two approaches. Results: The mean tumor diameter (range) was 7.0 cm (range 5.2–15.5 cm), and no significant differences were observed between the transperitoneal approach and retroperitoneal approach in any baseline clinical parameter. For right‐sided procedures, significant differences were found for operation time (113 vs 85 min), pneumoperitoneum time (93 vs 64 min) and estimated blood loss (96 vs 23 mL; P < 0.05, transperitoneal approach and retroperitoneal approach, respectively). No open conversion or recurrence was reported, but one right transperitoneal approach case required blood transfusion. No difference in these parameters was noted on the left side. Conclusions: For right side procedures, the retroperitoneal approach is feasible, safer and faster than the transperitoneal approach for large pheochromocytomas. Early transection of the feeding artery is beneficial for managing the tumor and reducing the risk of bleeding.